EFFECTIVENESS OF A COMBINED LABOR DANCE AND BIRTH BALL INTERVENTION IN REDUCING THE DURATION OF THE ACTIVE PHASE OF THE FIRST STAGE OF LABOR - Dolfina Welmina Juliana Tanlain; Gempi Tri Sumini; Dwi Retno Wati; Nurul Hidayati (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Prolonged labor remains a significant contributor to maternal and neonatal complications, particularly during the active phase of the first stage of labor. Non-pharmacological interventions, such as labor dance and birth ball exercises, have been proposed to facilitate labor progress by enhancing maternal comfort and promoting effective uterine contractions. Objective: This study aimed to examine the effectiveness of a combined labor dance and birth ball intervention in reducing the duration of the active phase of the first stage of labor. Methods: A quasi-experimental study with a post-test-only control group design was conducted among 30 laboring women in the active phase of the first stage of labor. Participants were selected using purposive sampling and assigned to either an intervention group, which received a combination of labor dance and birth ball exercises, or a control group that received standard care. The duration of the active phase was measured using an observation sheet and analyzed using an independent t-test. Result: The results demonstrated a statistically significant difference in the duration of the active phase between the intervention and control groups (p = 0.02). Women who received the combined labor dance and birth ball intervention experienced a shorter active phase compared to those in the control group. Conclusion: The combination of labor dance and birth ball exercises is effective in shortening the duration of the active phase of the first stage of labor. This intervention may serve as a safe, feasible, and non-pharmacological alternative to support normal labor progress in maternity care settings.